¡ESTO NO ES FICCIÓN!: LA EXPERIENCIA DE APRENDIZAJE DURANTE UNA PANDEMIA DESDE UNA ASIGNATURA DE CINE Y LITERATURA. - JURADO MUÑOZ, Andrea; RUIZ-BERDÚN, Dolores (Journal of Medicine & Movies / Revista de Medicina y Cine)
The year 2020 has transformed the lives of most of the world's inhabitants. A year ago, it would have been unimaginable to think that a situation like the present one could be real and not the result of a film belonging to the disaster genre. With this article we want to record the emotional and intellectual impact of the pandemic coinciding with the development of a transversal optional subject for Health Science degrees focused on the use of film and literature as teaching resources. The temporal coincidence of the beginning of the confinement to which the entire Spanish population was subjected with the development of the module on disasters and, more specifically, with the subject of epidemics, gave the rest of the subject a special atmosphere that we may never experience again, at least not with the same characteristics.